Awareness and Usage of Artificial Intelligence (AI) in Promoting Music Broadcast on Radio in Warri, Nigeria - Okpeki, Igue Philo; Onyenye, Temabor Peace (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper investigates the level of awareness and usage of artificial intelligence (AI) for promoting music broadcast on radio stations in Warri, Nigeria. The study was prompted by the paradigm shift that is brought about by the advent of artificial intelligence. Despite the advantages inherent in technology most radio stations appear to lack knowledge of the component meant for the broadcast of music. Thus, the study establishes the extent to which the radio station in Warri, Nigeria has become AI compliant in relaying music. To determine the AI awareness level and extent of usage in music promotion on radio stations, the researcher conducted interview sessions using four (4) radio stations, forty-one (41) on Air Personalities (OAP). A Self Respondent Interview Research Instrument was administered via email contact. The study was guided by three (3) research questions. Data were analyzed with the aid of percentage calculation measure to decide the level of awareness and usage of the AI tools connected to music broadcast on radio. The study found that respondents show low level of awareness of significant AI tools and thus could not deploy AI technologies for broadcast of music. The study concludes that it is important to create high level of awareness in the use of AI tools for promotion of music broadcast on radio. The study recommends that OAP should acquire the knowledge of AI tools related to promotion of music on radio stations. The proprietors of radio stations should provide training on the use of AI technologies to enable them become AI compliant in radio broadcasting.